The Role of the Fund in Governance Issues : Review of the Guidance Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
The Background Notes in this Supplement provide essential context and analysis needed to understand the problem of governance and corruption, its impact on the economies of Fund members, and the history and nature of Fund engagement on these issues. They also seek to support the assessment of the Fund's overall approach to promoting good governance and reducing corruption-including through the lenses of key stakeholders-with a view to identifying strength and closing any remaining gaps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet